Incidence and Risk Factors of Venous Thromboembolism in Patients After Transurethral Resection of the Prostate (TURP) - Zheng, Zhihuan; Wu, Ziqiang; Li, Kaixuan; Zhu, Quan; Li, Haozhen; Liu, Xuesong; Wang, Guilin; Tang, Zhengyan; Wang, Zhao (Frontiers in Surgery, 2022)
Objective: Venous thromboembolism (VTE) in patients following transurethral resection of the prostate (TURP) have been overlooked for many years. This research was aimed to investigate the incidence and risk factors of VTE in patients after TURP. Methods: A total of 451 patients underwent TURP between January 2017 and December 2020 were retrospectively analyzed. Clinical data of the patients were collected, Such as basic demographic data, prostate volume, creatinine values, hemoglobin values, surgery duration, Caprini score, IPSS score, QOL score, plasma D-dimer levels and so on. Univariate analysis and multivariate logistic regression were performed to identify the potential risk factors of VTE. Venous ultrasonography of lower extremities was performed routinely to detect VTE for patients after TURP. Results: 36 (8%) out of the 451 patients suffered from VTE. 12 (2.7%) patients were confirmed with deep venous thrombosis (DVT). 2 patients (0.4%) were identified with pulmonary embolism (PE). 22 (4.9%) patients were suffered from superficial venous thrombosis. Furthermore, according to the results of multivariate stepwise logistic regression analysis, having a history of VTE (aOR = 10.980, 95%CI = 2.265-53.223), complicated with postoperative bladder hematoma (aOR = 6.302, 95%CI = 2.265-17.532), D-dimer > 1.25 mg/L (aOR = 4.402, 95%CI = 1.798-10.774) and age > 65 were independent risk factors of VTE after TURP. And, the nomogram prediction model is a useful auxiliary prevention tool of VTE. Conclusion: The incidence of VTE is severely underestimated in patients following TURP. A lot of asymptomatic VTE have been overlooked. Early detection and diagnosis of VTE are essential. Nevertheless, further verifications based on the results of large scaled studies are still needed.